Social Cohesion, Religious Beliefs, and the Effect of Protestantism on Suicide - Becker, Sascha O.; Woessmann, Ludger (The Review of Economics and Statistics, 2018)
In an economic theory of suicide, we model social cohesion of the religious community and religious beliefs about afterlife as two mechanisms by which Protestantism increases suicide propensity. We build a unique microregional data set of 452 Prussian counties for 1816 to 1821 and 1869 to 1871, when religiousness was still pervasive. Exploiting the concentric dispersion of Protestantism around Wittenberg, our instrumental variable model finds that Protestantism had a substantial positive effect on suicide. Results are corroborated in first-difference models. Tests relating to the two mechanisms based on historical church attendance data and modern suicide data suggest that the sociological channel plays the more important role.